Synergistic effects of long‐wavelength ultraviolet A1 and visible light on pigmentation and erythema3. (2nd March 2018) - Kohli, I.; Chaowattanapanit, S.; Mohammad, T.F.; Nicholson, C.L.; Fatima, S.; Jacobsen, G.; Kollias, N.; Lim, H.W.; Hamzavi, I.H.
Summary: Background: Visible light (VL) induces multiple cutaneous effects. Sunscreen testing protocols recommended by regulatory bodies throughout the world require the use of solar simulators with spectral output in the ultraviolet (UV) domain only. However, sunlight contains VL and infrared radiation also. Objectives: This study aimed to evaluate the contributions of VL and UVA on pigmentation and erythema, and optimize parameters for in vivo testing. Methods: Ten subjects with Fitzpatrick skin phototype IV–VI were enrolled. Subjects were irradiated on their back with VL using two light sources: one containing pure VL and one containing VL with less than 0·5% UVA1 (VL+UVA1). Four different irradiances were administered to investigate reciprocity behaviour. Assessments, including photography, Investigator's Global Assessment, colorimetry and spectroscopy, were performed immediately, 24 h, 7 days and 14 days post‐irradiation. Results: Pigmentation was observed with both light sources; however, pigment intensity was greater with VL+UVA1 than with pure VL. Reciprocity was observed in pure VL sites, but not VL+UVA1. Variation in spectral output had greater impact on pigment intensity than irradiance. Clinical erythema was observed on the VL+UVA1 side, but not on the pure VL side. A protocol for testing photoprotection product efficacy against VL‐induced effects has been proposed. Conclusions: The findings suggest a synergistic relationship between VL and UVA1 and emphasize the need for developing means of photoprotection against VL. Abstract : What's already known about this topic? Visible light (400–700 nm) (VL) induces dark and persistent pigmentation, erythema, DNA damage secondary to free radical production and exacerbation of photodermatoses. In the U.S.A., sunscreens with critical wavelength (wavelength with 90% of area under the absorbance spectra when integrating from 290 nm to 400 nm) ≥ 370 nm can claim broad‐spectrum photoprotection. Criteria in the European Union and Australia require the ratio of sun protection factor to ultraviolet A (UVA) protection factor to be ≤ 3 : 1. What does this study add? The findings demonstrate a synergistic relationship between VL and long‐wavelength UVA1 (370–700 nm). These effects emphasize the need for photoprotection against this part of the solar spectrum. A protocol for testing photoprotection product efficacy against VL‐induced effects has also been proposed. Respond to this article Plain language summary available online